Basophils in inflammation - Schwartz, Christian; Eberle, Jörg; Vöhringer, David (European Journal of Pharmacology, 2015)
Basophils are functionally closely related to mast cells. Both cell types express the high-affinity IgE receptor (Fc?RI) and rapidly release preformed mediator from intracellular stores upon IgE-mediated activation. However, in contrast to mast cells basophils finish their maturation in the bone marrow and have a lifespan of only 2-3 days. Basophil numbers increase in response to IL-3 or TSLP and migrate into tissues to promote type 2 immune responses. Here we review recent advances regarding the pro- and anti-inflammatory functions of basophils in murine models and human allergic inflammation of the skin, lung and intestine.
EVALuna2:25875

Eosinophils Mediate Basophil-Dependent Allergic Skin Inflammation in Mice - Eberle, Jörg; Radtke, Daniel; Nimmerjahn, Falk; Vöhringer, David (Journal of Investigative Dermatology, 2019)
The mechanisms leading to allergic skin inflammation, such as atopic dermatitis or urticaria, are poorly defined. Here we used a mouse model for IgE-dependent chronic allergic inflammation to study the role of basophils and eosinophils for induction of pathology. FcεRI expression in basophils was required for the ear swelling response, and basophils promoted the expression of eosinophil-recruiting chemokines in the ear. The ear swelling response could be prevented by prior infection of mice with helminths in an IgE-dependent manner. Impaired skin eosinophilia and reduced ear swelling was further observed in IL-4/IL-13–deficient and STAT6-deficient mice. In addition, eosinophil-deficient ΔdblGATA mice showed only weak ear swelling response, which could be enhanced by eosinophil transfer. This suggests that IgE-activated basophils orchestrate the recruitment of eosinophils by secretion of IL-4/IL-13, which leads to STAT6-dependent expression of CCL24 from endothelial cells and extravasation of eosinophils into the ear pinna. Eosinophils are then the critical effector cells that cause pathology. Therefore, combined therapeutic approaches that block basophil activation and reduce eosinophil numbers could be efficient strategies to improve treatment of chronic allergic disorders of the skin.
CRIS-Team Scopus Importer:2019-07-02

Opposing functions of thymic stromal lymphopoietin-responsive basophils and dendritic cells in a mouse model of atopic dermatitis - Schwartz, Christian; Eberle, Jörg; Hoyler, Thomas; Diefenbach, Andreas; Lechmann, Matthias; Vöhringer, David (Journal of Allergy and Clinical Immunology, 2016)
EVALuna2:25878

Role of basophils in protective immunity to parasitic infections - Eberle, Jörg; Vöhringer, David (Seminars in Immunopathology, 2016)
Basophils have been recognized as important players for protective immunity against a variety of different endo- and ectoparasites. Although basophils represent a relatively rare and short-lived cell type, they produce large quantities of effector molecules including histamine, cytokines, chemokines, and lipid mediators which promote type 2 immune responses. Basophils can be activated either directly by parasite-derived factors or indirectly by recognition of parasite-derived antigens via IgE bound to its high-affinity receptor Fc?RI on the cell surface. Many parasitic infections cause expansion and tissue recruitment of basophils, but the role of basophils for protective immunity remains poorly understood. The development of basophil-deficient mouse models over the past few years makes it possible to study their contributions in various infections. We review here the current knowledge regarding the role of basophils for protective or immunomodulatory functions of basophils mainly during infections of mice with protozoan parasites, helminths, and ectoparasites.
EVALuna2:25880

Smart forecasting of artifacts in contrast-enhanced breast MRI before contrast agent administration - Liebert, Andrzej; Das, Badhan Kumar; Kapsner, Lorenz; Eberle, Jörg; Skwierawska, Dominika; Folle, Lukas; Schreiter, Hannes; Laun, Frederik Bernd; Ohlmeyer, Sabine; Uder, Michael; Wenkel, Evelyn; Bickelhaupt, Sebastian (European Radiology, 2023)
Objectives: To evaluate whether artifacts on contrast-enhanced (CE) breast MRI maximum intensity projections (MIPs) might already be forecast before gadolinium-based contrast agent (GBCA) administration during an ongoing examination by analyzing the unenhanced T1-weighted images acquired before the GBCA injection. Materials and methods: This IRB-approved retrospective analysis consisted of n = 2884 breast CE MRI examinations after intravenous administration of GBCA, acquired with n = 4 different MRI devices at different field strengths (1.5 T/3 T) during clinical routine. CE-derived subtraction MIPs were used to conduct a multi-class multi-reader evaluation of the presence and severity of artifacts with three independent readers. An ensemble classifier (EC) of five DenseNet models was used to predict artifacts for the post-contrast subtraction MIPs, giving as the input source only the pre-contrast T1-weighted sequence. Thus, the acquisition directly preceded the GBCA injection. The area under ROC (AuROC) and diagnostics accuracy scores were used to assess the performance of the neural network in an independent holdout test set (n = 285). Results: After majority voting, potentially significant artifacts were detected in 53.6% (n = 1521) of all breast MRI examinations (age 49.6 ± 12.6 years). In the holdout test set (mean age 49.7 ± 11.8 years), at a specificity level of 89%, the EC could forecast around one-third of artifacts (sensitivity 31%) before GBCA administration, with an AuROC = 0.66. Conclusion: This study demonstrates the capability of a neural network to forecast the occurrence of artifacts on CE subtraction data before the GBCA administration. If confirmed in larger studies, this might enable a workflow-blended approach to prevent breast MRI artifacts by implementing in-scan personalized predictive algorithms. Clinical relevance statement: Some artifacts in contrast-enhanced breast MRI maximum intensity projections might be predictable before gadolinium-based contrast agent injection using a neural network. Key Points: • Potentially significant artifacts can be observed in a relevant proportion of breast MRI subtraction sequences after gadolinium-based contrast agent administration (GBCA). • Forecasting the occurrence of such artifacts in subtraction maximum intensity projections before GBCA administration for individual patients was feasible at 89% specificity, which allowed correctly predicting one in three future artifacts. • Further research is necessary to investigate the clinical value of such smart personalized imaging approaches.
CRIS-Team Scopus Importer:2023-12-22
Keywords: Artifact; Breast; Forecasting; Magnetic resonance imaging; Neural networks (computer)